UNCERTAINTY, CHANGEABILITY AND INCONSISTENCY IN TASKS OF ANALYZING RISKS OF ECONOMIC SYSTEM BEHAVIOR - V. I. Avdiyskiy (Real Economics Publishing House, 2014)
The theorem of ultimate uncertainty of a complex economic system states that the social-economical process of a complex economic system functioning develops efficiently if complexity and manageability characteristics are similar, and manageability criteria correspond to the levels of uncertainty of the environment and organization, and subsequently, its risk levels and management systems. The theorem of ultimate uncertainty (manageability) also allows making some individual conclusions. For example, taking into account uncertainty levels, we can select instruments for analysis, quantitative and qualitative methods of estimating possible risk development and means for its regulation.